I gränslandet: Norm- och ekokritiska perspektiv på Inga Borgs böcker om Plupp - Graeske, Caroline (Tidskrift för litteraturvetenskap, 2020)
Beyond Borders. Norm- and Ecocritical Perspectives on Inga Borg’s Plupp Series The aim of this article is to study how Sami environments are represented in Inga Borg’s Plupp books. How are the characters portrayed and how do they relate to each other and to the environment? In the analysis, ecocritical and postcolonial theories are used. The result shows that Plupp is a character who interacts with nature and animals and follows the shifts of nature. Several books contain ecocritical motifs and Plupp shows great hospitality and generosity and he also advocates biodiversity and variety. In the characterisation of Plupp, rudimentary binaries like nature-culture and male-female are deliberately superseded or harmonised. Plupp can thus be read as a metaphor of equality, but also as a recognition of the Other. As a person (or being) seemingly existing in a space beyond language, Plupp transcends the expectations and limitations of many normative categorisations.